2014
DOI: 10.1590/rou.2014.029
|View full text |Cite
|
Sign up to set email alerts
|

Lesões maxilofaciais: um levantamento de 762 casos da Universidade Federal de Sergipe, Brasil

Abstract: ResumoIntrodução: A pesquisa epidemiológica de lesões maxilofaciais em determinada região estabelece as necessidades populacionais e orienta os profissionais da saúde na definição de ações preventivas e tratamento adequado. Objetivo: Analisar os laudos histopatológicos de lesões maxilofaciais do período de 1996 a 2011 do Laboratório de Patologia Oral do Departamento de Odontologia da Universidade Federal de Sergipe (UFS), Brasil. Material e método: Estudo retrospectivo das biópsias realizadas de 1996 a 2011, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 25 publications
(36 reference statements)
4
8
1
Order By: Relevance
“…In the present study, the most prevalent cases were female patients with lesions in the posterior region of the mandible. A higher frequency of females and mandibular involvement in patients with bone -related lesions of the jaws were also described by Souto et al 6 and Jaafari and Akbari. 1 This agreement can be justified not specifically due to it affecting more women, but possibly due to women being more aware of their health needs and possible alterations than men.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the present study, the most prevalent cases were female patients with lesions in the posterior region of the mandible. A higher frequency of females and mandibular involvement in patients with bone -related lesions of the jaws were also described by Souto et al 6 and Jaafari and Akbari. 1 This agreement can be justified not specifically due to it affecting more women, but possibly due to women being more aware of their health needs and possible alterations than men.…”
Section: Discussionsupporting
confidence: 67%
“…In this study, it was 45,23 years. Souto et al, 6 in a survey of 762 cases of maxillofacial lesions, had a patients' mean age of 34 years. On the other hand, Jaafari and Akbari 1 had an average age of 28 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study analyzed 3,068 histopathology reports, among which 16.9% represented oral neoplasms. In the study by Trevisan et al 5 that was conducted over a 12-year period, 21.4% of the 707 histopathology reports of lesions submitted for biopsy were of oral neoplasms and 19% of the 762 cases analyzed in the 16-year retrospective study conducted by Souto et al 4 included benign and malignant neoplasms of the oral cavity. Thus, it is observed that neoplasms represent a significant portion of the total lesions that affect the oral and maxillofacial complex and, therefore, an epidemiological study evaluating the occurrence of such lesions is of great importance so that the dentist can make a decision about the best therapeutic option, as well as about possible preventive measures 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies that consider case series of neoplasms and dysplastic lesions have been conducted in Brazil. Studies of this nature enable the identification of the user profiles of the service in question and, indirectly, recommendation of the possible strategic actions to be implemented for dealing with the oral condition of a given population [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%